Air Pollution Dynamics: Insights into Current Condition of Policy Framework and Future Strategy - Yopik Gani; Saut Panggabean Sinaga (Universitas Sultan Ageng Tirtayasa, 2023)
This comprehensive study examines the complex phenomenon of air pollution in Indonesia, providing insights into various aspects such as current conditions, the policy framework, and potential strategies ahead. By conducting a comprehensive review of relevant literature and employing novel methods to analyze Google Trends data, a meticulous examination of prevailing themes and public inquiries is revealed. Significantly, there is an increasing societal awareness of air pollution's condition, effects, and regulation, especially in urban cities, in August 2023. This study not only highlights the current difficulties but also delves into potential lessons learned by other countries and provides valuable suggestions. This paper makes a valuable contribution to the field of air pollution mitigation policies and environmental management. This study provides policymakers, industries, and communities with a comprehensive framework to address air pollution problems. This comprehensive study allows relevant stakeholders to adopt strategies that lead to a more environmentally sustainable Indonesia.